Pathogenicity of symbiotic bacteria associated with entomopathogenic nematodes on larvae of Galleria mellonella - Vinay Kumar, S; Mulla, S R; C, Sandeep; Suresh, C K (Journal of Phytology, 2011)
The investigation was carried out to study the effect of different population of symbiotic bacteria associated with entomopathogenic nematodes isolated from agroclimatic zone 5 of Karnataka on second instar larvae of greater wax moth, Galleria mellonella by artificial diet method. Entomopathogenic nematodes were isolated by insect bait method and symbiotic bacteria were isolated and identified by morphological and biochemical tests. Second instar larvae of G. mellonella were fed with artificial diet containing different populations of bacterial cells and mortality data of larvae was recorded after 48hrs. The cumulative mortality of larvae has increased with increase in the concentration of bacterial cells. The median lethal concentration varied among the bacterial isolates against G.mellonella larvae. Among the twenty isolates used in the study, isolate KPR1 was found to be highly pathogenic with a lower median lethal concentration of 0.018x105 cells/ml followed by HEB2 (0.084x105 cells/ml), KPR4 (0.12x105 cells/ml), CHK1(0.13x105 cells/ml), KPR3(0.16x105 cells/ml), EXP2 (0.19x105 cells/ml) CHK2 (0.19x105 cells/ml), RMG2(0.20x105 cells/ml). The remaining twelve bacterial isolates showed higher median lethal concentration with isolate BGR showing the highest LD50 of 26x105 cells/ml. These results suggest that the toxic activity to G. mellonella varied among the Symbiotic bacteria isolated from different locations.